2007
DOI: 10.1152/ajpcell.00202.2007
|View full text |Cite
|
Sign up to set email alerts
|

Rodent intestinal folate transporters (SLC46A1): secondary structure, functional properties, and response to dietary folate restriction

Abstract: This laboratory recently identified a human gene that encodes a novel folate transporter [Homo sapiens proton-coupled folate transporter (HsPCFT); SLC46A1] required for intestinal folate absorption. This study focused on mouse (Mus musculus) PCFT (MmPCFT) and rat (Rattus norvegicus) PCFT (RnPCFT) and addresses their secondary structure, specificity, tissue expression, and regulation by dietary folates. Both rodent PCFT proteins traffic to the cell membrane with the NH(2)- and COOH-termini accessible to antibod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
154
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(167 citation statements)
references
References 35 publications
13
154
0
Order By: Relevance
“…The K m value (2.14 碌M) determined for L-MTX in the current study was found to be similar to those reported previously in a range of different systems, including 0.6-2.6 碌M in HepG2 cells transfected with rPCFT cDNA, 21) 5.7 碌M in Xenopus oocytes injected with rPCFT cRNA, 22) and 1.0-4.6 碌M in HepG2 cells transfected with mouse PCFT cDNA. 21) The Dixon plot showed that the uptake of L-MTX was inhibited in a competitive manner by unlabeled L-MTX, which gave a K i value of 1.25 碌M.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The K m value (2.14 碌M) determined for L-MTX in the current study was found to be similar to those reported previously in a range of different systems, including 0.6-2.6 碌M in HepG2 cells transfected with rPCFT cDNA, 21) 5.7 碌M in Xenopus oocytes injected with rPCFT cRNA, 22) and 1.0-4.6 碌M in HepG2 cells transfected with mouse PCFT cDNA. 21) The Dixon plot showed that the uptake of L-MTX was inhibited in a competitive manner by unlabeled L-MTX, which gave a K i value of 1.25 碌M.…”
Section: Discussionsupporting
confidence: 90%
“…21) The Dixon plot showed that the uptake of L-MTX was inhibited in a competitive manner by unlabeled L-MTX, which gave a K i value of 1.25 碌M. It is noteworthy that this K i value is almost equal to the K m value (2.14 碌M) of L-MTX.…”
Section: Discussionmentioning
confidence: 95%
“…For >60 y, folate analogs that inhibit intracellular folate-using enzymes, termed antifolates, have been developed to treat a variety of cancer types and inflammatory diseases (8)(9)(10)(11)(12)(13)(14). More recently, the emphasis in folatemediated drug therapy has shifted to obtain a better understanding of transport mechanisms of antifolates because dose-limiting toxicities arise from their transport via RFC, and possibly PCFT, into normal cells (6,11,(15)(16)(17). To date, antifolates approved for clinical use are transported primarily via RFC, although one of the most recently developed antifolates, pemetrexed (PMX), may also transit through PCFT (6,11,(18)(19)(20)(21).…”
mentioning
confidence: 99%
“…There are two N-glycosylation consensus sites (Asn-58 and Asn-68) in the hPCFT loop domain between transmembrane domains (TMDs) 1 and 2. Based on results with substituted cysteine-scanning mutagenesis of a Cys-less hPCFT and accessibilities to thiol-reactive agents (27) and on studies of hemagglutinin (HA) epitope accessibilities to epitope-specific antibody (28,29), hPCFT has 12 TMDs with N and C termini directed to the cytosol. Structurally and/or functionally important residues have been identified in hPCFT and include (with possible roles) Glu-185 (which is required for proton coupling) (30), His-247 and Ser-172 (which modulate folate and proton access to a high affinity binding site) (31), His-281 (which is important for substrate binding) (31), Arg-376 (which impacts proton and substrate binding) (12), and Asp-156 (which contributes to PCFT protein stability) (13) (Fig.…”
mentioning
confidence: 99%